If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 2 = 3a + -6 Reorder the terms: 2 + a = 3a + -6 Reorder the terms: 2 + a = -6 + 3a Solving 2 + a = -6 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 2 + a + -3a = -6 + 3a + -3a Combine like terms: a + -3a = -2a 2 + -2a = -6 + 3a + -3a Combine like terms: 3a + -3a = 0 2 + -2a = -6 + 0 2 + -2a = -6 Add '-2' to each side of the equation. 2 + -2 + -2a = -6 + -2 Combine like terms: 2 + -2 = 0 0 + -2a = -6 + -2 -2a = -6 + -2 Combine like terms: -6 + -2 = -8 -2a = -8 Divide each side by '-2'. a = 4 Simplifying a = 4
| -3+7x=18 | | 24x^9y^12+40x^3y^3=0 | | 54x^2y^8+12x^2y^4=0 | | (x-4)(5x+7)=0 | | -9.9x=19.8 | | 3(y-1)+9=8y+6-5y | | f-9=4-9+3-9+2 | | 0.5y^2+0.6y^2-0.3y^2= | | 0.1(x+10)=0.3x-4 | | -9(3b+3)+(28b-3)=0 | | 0.25x+0.05(4-x)=0.10(38) | | -8x-x= | | 21x-63+6x+240=420 | | 26+x+17=-42 | | 9x-3y=9 | | 6-(2x-4)+x=3(x-4) | | 4.8q-1.2-4.6q=-0.8q-2.6 | | -6+2-5x+7+x=39 | | 5.3q-1.3-5.6q=1.3q-1.9 | | 1+11x=-9 | | 20+x=52 | | 20+26x=52 | | -8y-14=5y+12 | | -3y+3=-4y+9 | | 8-7x=-29 | | 3x+1.5x=90 | | 4(x-3)+2=2x+12 | | 3a+1b=2 | | 2(1.5x-1.2)=-12.3 | | 18-3x=-14 | | 10x+3=4x-15 | | 11a-6(a+4)= |